The Role of Physical Activity Behavior in the Mental Wellbeing of Vocational Education and Training Students: The PHIT2LEARN Study - Kirschner, Mara; Golsteijn, Rianne H. J.; van der Wurff, Inge S. M.; Savelberg, Hans H. C. M.; de Groot, Renate H. M. (Frontiers in Education, 2022)
A positive association has been found between physical activity (PA) and student mental wellbeing (SMW). This association has been mainly explored in secondary school and university students. Studies in vocational education and training (VET) are lacking, while VET students could especially benefit from exploring this association since research shows that VET students, who often come from low socioeconomic status (SES) households, are prone to low SMW. Low SMW can result in higher school dropout rates and long-term negative effects, such as unemployment, social exclusion, and impoverishment. The aim of the current study was to explore the association between total PA and different physical activity behaviors PABs, i.e., moderate to vigorous physical activity (MVPA), light physical activity (LPA), and sedentary behavior (SB), and SMW in the VET setting. In this cross-sectional observational study, students wore an ActivPAL3™ accelerometer for 7 consecutive days to measure PAB. SMW was assessed using the Center for Epidemiologic Studies Depression Scale (CES-D) and the Rosenberg self-esteem questionnaire (RSE). Complete data for the analyses were obtained from 85 students. Multiple regression analyses showed a significant positive association between total PA and self-esteem and a significant negative association between total PA and depressive symptoms. Taking different PA intensities into account, there was a significant positive association between LPA and self-esteem and a significant negative association between LPA and depressive symptoms. No significant associations were found between MVPA and the outcome measures, although the associations were aligned with the findings for LPA. High levels of SB were significantly associated with low self-esteem; however, the association between SB and depressive symptoms was not significant. The significant positive associations between LPA and SMW and the negative association between SB and self-esteem indicate that decreasing SB and increasing LPA could contribute to improve SMW. Future research should determine if these are causal relationships.